2012
DOI: 10.1111/j.1600-079x.2012.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents hemorrhagic shock‐induced liver injury in rats through an Akt‐dependent HO‐1 pathway

Abstract: Although melatonin treatment following trauma-hemorrhage or ischemic reperfusion prevents organs from dysfunction and injury, the precise mechanism remains unknown. This study tested whether melatonin prevents liver injury following trauma-hemorrhage involved the protein kinase B (Akt)-dependent heme oxygenase (HO)-1 pathway. After a 5-cm midline laparotomy, male rats underwent hemorrhagic shock (mean blood pressure approximately 40 mmHg for 90 min) followed by fluid resuscitation. At the onset of resuscitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
2
19
0
1
Order By: Relevance
“…Thus, there is an urgent need to develop antioxidative therapeutic options and identify protective agents for ameliorating Cd‐induced damage. Melatonin is a powerful endogenous antioxidant secreted by the pineal gland and possesses potent hepatoprotective properties against the development and progression of acute and chronic liver injury . In the present study, we found that melatonin treatment significantly alleviated Cd‐induced liver injury by decreasing serum ALT/AST levels and suppressing the production of pro‐inflammatory cytokines such as IL‐1β, TNF‐α, and IL‐6.…”
Section: Discussionsupporting
confidence: 60%
“…Thus, there is an urgent need to develop antioxidative therapeutic options and identify protective agents for ameliorating Cd‐induced damage. Melatonin is a powerful endogenous antioxidant secreted by the pineal gland and possesses potent hepatoprotective properties against the development and progression of acute and chronic liver injury . In the present study, we found that melatonin treatment significantly alleviated Cd‐induced liver injury by decreasing serum ALT/AST levels and suppressing the production of pro‐inflammatory cytokines such as IL‐1β, TNF‐α, and IL‐6.…”
Section: Discussionsupporting
confidence: 60%
“…Melatonin also reduces cytokine levels in surgical neonates [12]. Melatonin prevents hemorrhagic shock-induced liver injury in rats through an Akt-dependent HO-1 pathway [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Animals were fasted for 8 h before the experiment but had free access to water ad libitum. A nonheparinized model of trauma-hemorrhagic shock was used as described previously (11,12). At the time of the experiment, the rats were breathing in 100% O 2 and anesthetized by isoflurane inhalation (1.2%) using anesthesia vaporizer (VIP-3000, Paragon Medical, Coral Springs, FL) before the induction of soft-tissue trauma via only 5-cm midline laparotomy.…”
Section: Methodsmentioning
confidence: 99%